O gênero da política brasileira: questões de igualdade no Senado Federal - Brasil, Patricia Cristina (2016)
Despite all progress made in regards of the recognition of women's rights in recent decades, yet there is a deep gap between the formal recognition of equality between men and women and its real achievement. By the various reported and exposed indexes in this research, it is perceived that there is a culture in transition, with strong patriarchal traits and male domination, which are reflected on the organization of social life, especially in politics and law, always considered territories inherent to men. The persistence of gender inequality in public spaces of power a situation which, from the consolidation of Brazilian democracy and especially after the 1990s, is of concern to government's agenda, movements for women rights and the international community motivates this work. The publishing of several national and international reports informs the maintenance of under-representativeness of women in Brazil, especially in places of representation such as the Legislative Power, despite inclusion efforts such as the establishment of application quotas. The lack of presence and, therefore, the absence of women experience in spaces of political construction as well as in Law impact negatively on the quality of democracy built in Brazil after the military regime. We intend, with the presented study , analyze and understand the dynamics of inclusion and existing gender inequality in Brazilian politics , trying to capture the role of institutions in the production and reproduction of this discrepancy and how it relates to the process of government in presidentialism coalition , pointing partisan barriers that hinder women's access to public office , as well as the quantitative impact of this under-representation in the activities of the Senate, as the legislative production and the establishment of agendas. Much of studies conducted in the country on the theme , focuses on the underrepresentation of women in politics restrictively the scope of the Chamber of Deputies, bypassing the analysis of gender relations in the Senate. Thus, the study aims the understanding of a social justice issue, which is gender inequality in positions of power, from an institutional point of view of the Democratic State of Law, having the Brazilian Federal Senate in its 54th Legislature, covering the years 2011-2015, as the research locus.